On the picture dependence of Ramond-Ramond cohomology - Berkovits, Nathan [UNESP]; Zwiebach, Barton (Elsevier, 1998)
Closed string physical states are BRST cohomology classes computed on the space of states annihilated by b- 0. Since b- 0 does not commute with the operations of picture changing, BRST cohomologies at different pictures need not agree. We show explicitly that Ramond-Ramond (RR) zero-momentum physical states are inequivalent at different pictures, and prove that non-zero-momentum physical states are equivalent in all pictures. We find that D-brane states represent BRST classes that are non-polynomial on the superghost zero-modes, while RR gauge fields appear as polynomial BRST classes. We also prove that in x-cohomology, the cohomology where the zero-mode of the spatial coordinates is included, there is a unique ghost-number one BRST class responsible for the Green-Schwarz anomaly, and a unique ghost number minus one BRST class associated with RR charge. © 1998 Elsevier Science B.V.